Evidence of estrus before CIDR insertion does not influence pregnancy rate to fixed-timed artificial insemination in beef heifers - Johnson, Sandra K.; Ward, M.A.; Swanson, O.L.; Perry, G.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Protocols used for fixed-timed artificial insemination strive to synchronize growth of follicular waves and commonly do so by administration of gonadotropin-releasing hormone (GnRH) at the beginning of the treatment. The stage of the cycle at the time of GnRH injection influences the proportion of animals that respond, and cows respond more consistently than heifers. Variability in response to GnRH has been offered as an explanation for why why short-term fixed-timed insemination protocols tend to be less effective in heifers than cows. The dairy industry has used prostaglandin (PG) to “pre-synchronize” cow ovulation before a protocol to improve the proportion of cows that initiate a new wave of follicular growth. Because of the additional cost in time and product, the beef industry has been reluctant to explore this approach. South Dakota State University research has indicated that variability in onset of estrus was reduced when PG was given 3 days before a controlled internal drug release (CIDR) protocol. A reduction in variability of the onset of estrus may improve response to fixed-time artificial insemination. The objective of this study was to determine if the onset of estrus prior to a PG 6-day CIDR protocol would improve pregnancy rates to fixed-time artificial insemination in beef heifers.
Keywords: Cattle; CIDR; Pregnancy Rate; Artificial insemination; Gonadotropin-releasing hormone (GnRH)